Organisational downsizing and increased use of psychotropic drugs among employees who remain in employment - Kivimäki, Mika (BMJ Group, 2007)
OBJECTIVE: Organisational downsizing is common in modern work life, but its effect on employees' mental health is not known. The authors examined whether working in downsizing organisations predicts use of psychotropic drugs among employees who remain in employment. DESIGN, SETTING AND PARTICIPANTS: Prospective cohort study of municipal employees in Finland. 4783 employees worked in downsized units but kept their jobs after downsizing in 1993, 4271 employees lost their jobs during the downsizing, and 17 599 employees did not experience downsizing. The outcome was psychotropic drug prescriptions (antidepressants, anxiolytics and hypnotics) during 1994–2000 extracted from nationwide registers and linked to the data by means of each participant's personal identification number. MAIN RESULTS: After adjustment for predownsizing characteristics, employees who were exposed to downsizing but kept their jobs were at a higher risk of being prescribed psychotropic drugs (rate ratio 1.49, 95% CI 1.10 to 2.02 in men and 1.12, 95% CI 1.00 to 1.27 in women) than those not exposed to downsizing. The association of downsizing was strongest with hypnotics among the men and with anxiolytics among the women. An increased rate of psychotropic prescriptions after downsizing was also seen in male workers who lost their job (rate ratio 1.64, 95% CI 1.19 to 2.25). CONCLUSIONS: The association between organisational downsizing and increased use of psychotropic drugs suggests that this managerial strategy may pose mental health risks among employees.